Aplikasi Jenis Umbi dan Konsentrasi Gula Pasir Terhadap Tingkat Keberhasilan Bibit Jamur Tiram - Kholifatul Laila; Wening Kusuma Wardani (Indonesian Journal of Applied Science and Technology, 2020)
This study aims to determine effect of various tuber media, sugar concentration, and combination of both factors on success of white oyster mushroom F0 seeds, carried in Mapin Kebak Village Sumbawa Regency, from May-June 2018. Using quantitative method research, factorial Completely Randomized Design (CRD) with two factors. The first factor was various tuber media (M) with 4 experimental levels, namely M0(potato), M1(white sweet potato), M2(cassava), and M3(Amorphopalus). The second factor was sugar consentration (G) with 3 experimental levels, namely G0(10 gr/l), G1(20 gr/l), G2(25 gr/l), there are 12 treatments with 7 replications and 84 test units. The conclusions are: a)the thickest mycelium on media surface on third week is M0(potato, the longest length of mycelium on first week is M1(white sweet potato) and on third week is M0 (potato), the fastest growth rate of mycelium on first week is M1(white sweet potato), on second and third week is M0(potato); b)the thickest mycelium on media surface on first week and the length of the mycelium displayed on second week is G1(concentration of sugar 20g/l); c)the longest mycelium is M0G1(potatoes+granulated sugar 20g/l) on third week and the lowest level of contamination of combination is M1G0(white sweet potato+granulated sugar 10g/l).